Efficient (S)-acetoin production in Saccharomyces cerevisiae by modulating α-acetolactate decarboxylase stereospecificity - Cha, Seungwoo; Jang, Byeongseon; Lee, Daeyeol; Cho, Injae; Park, Wooyoung; Lee, Youngmin; Shin, Hyesoo; Kim, Minyoung; Sung, Chang min; Hahn, Ji-Sook (Elsevier BV, 2025)
Acetoin, a four-carbon alpha-hydroxyketone with a chiral center, exists as two stereoisomers-(R)- and (S)-acetoin-both of which hold potential pharmaceutical applications. While microbial production of (R)-acetoin has been well studied, fermentative production of (S)-acetoin remains limited due to its reliance on non-enzymatic spontaneous decarboxylation of unstable intermediates. As a result, costly precursors like diacetyl or 2,3-butanediol are often used, posing challenges for economic scale-up. In this study, we engineered Saccharomyces cerevisiae to produce stereospecific (S)-acetoin directly from glucose, a low-cost and abundant carbon source. The native racemic acetoin pathway was eliminated by disrupting pyruvate decarboxylase (PDC) activity, and the stereospecificity of Bacillus subtilis alpha-acetolactate decarboxylase (ALDC), which naturally favors (R)-acetoin, was engineered to preferentially produce (S)-acetoin. Oxygen uptake was genetically enhanced to support efficient conversion of intermediates and suppress byproducts. This work established a novel, enzyme-driven pathway for (S)-acetoin biosynthesis with over 90% enantiomeric purity, without the addition of chemical compounds.